LOC285194 inhibits proliferation of human keratinocytes through regulating miR-616/GATA3 pathway. (October 2020) - Lin, Jin; Fang, Yimiao; Tao, Maocan; Ma, Lili; Cao, Yi; Li, Yuanyuan; Ji, Cheng; Yang, Jia; Yang, Xiaohong
Abstract: LncRNA LOC285194 has been associated with the occurrence of psoriasis. However, the underlying mechanisms that lead to psoriasis remain unclear. In this study, the expression of LOC285194, miR-616, and GATA3 was determined by western blotting and quantitative real-time PCR, and their relationships were assessed using dual-luciferase reporter assays. The effects of LOC285194 on the proliferation and apoptosis of keratinocytes were investigated using cell counting kit-8 assays and flow cytometry, respectively. Reduced expression of LOC285194 was detected in the skin lesion samples from patients with psoriasis. Overexpression of LOC285194 led to reduced cell viability, cell cycle arrest, and increased cell apoptosis in keratinocytes, whereas LOC285194 silencing resulted in opposite effects. In addition, LOC285194 was found to negatively regulate miR-616, which modulated GATA3 expression through its direct binding to the 3′-untranslated region of GATA3. Knockdown of GATA3 rescued LOC285194 overexpression-mediated cell viability reduction, cell cycle arrest and apoptosis induction in keratinocytes. Taken together, LOC285194 was found to inhibit keratinocyte growth by sponging miR-616 that regulates GATA3. Highlights: LOC285194 was low expressed in psoriasis. Keratinocytes growth was inhibited by overexpressing LOC285194. Keratinocytes apoptosis was promoted by overexpressing LOC285194. LOC285194 sponged miR-616. LOC285194 up-regulated GATA3 expression through miR-616.